Stature estimation by ct scan images of metacarpal measurements in malaysian malay males. - Abu Bakar S.N.; Abdullah N.; Noor M.H.M.; Shafie M.S.; Alias A.; Ibrahim A.; Nor F.M. (All India Institute of Medical Sciences, 2024)
Indexed by Scopus